2022
DOI: 10.7759/cureus.20888
|View full text |Cite
|
Sign up to set email alerts
|

Is Acupuncture Safe and Effective Treatment for Migraine? A Systematic Review of Randomized Controlled Trials

Abstract: Migraine is a debilitating condition that places a substantial economic burden on society and seriously affects patients' quality of life. Currently, there is no known "cure" for migraines, and pharmacologic treatments or prophylaxis carry many unwanted effects. Acupuncture has been accepted as an alternative treatment. However, its effectiveness is still debated. This is a systematic review of randomized controlled trials (RCT) that investigate acupuncture safety and efficacy in migraine versus various contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
(150 reference statements)
1
12
0
Order By: Relevance
“…Even the latest publications on acupuncture alone for treating migraine have shown the same results as the current review, thus demonstrating that follow-up for this pathology must be applied effectively to determine the presence of a positive or long-term effect (Naguit et al, 2022). Another finding was the small number of studies of high relevance included in the final screening.…”
Section: Discussionsupporting
confidence: 68%
“…Even the latest publications on acupuncture alone for treating migraine have shown the same results as the current review, thus demonstrating that follow-up for this pathology must be applied effectively to determine the presence of a positive or long-term effect (Naguit et al, 2022). Another finding was the small number of studies of high relevance included in the final screening.…”
Section: Discussionsupporting
confidence: 68%
“…[40] Naguit Noreen study found that acupuncture could be used as an alternative or adjunctive therapy for the treatment of episodic headache. [41] Beier Dagmar study provided an updated guide to some of the most widely used non-pharmacological treatments for migraine. [42] Guidelines suggest that physical activity may have a positive effect on quality of life, with acupuncture having a positive impact on headache frequency, intensity, quality of life, and aggressive drug use.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing collection of credible research shows that acupuncture can greatly reduce the symptoms of migraines. [22][23][24] , and many headache clinical practice standards include recommendations for the treatment of migraine with or without acupuncture, although the quality of these suggestions varies. This study analyzed the recommendations for acupuncture in global headache guidelines and identi ed many issues to clarify the current status of acupuncture recommendations for migraine in global headache guidelines and to develop standardized recommendations for acupuncture for migraine in future international guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A rising number of high-quality clinical studies [22][23][24] have recently provided evidence that acupuncture is actually an effective therapy for migraines, supporting the thousands of years of usage of the practice in China. Despite the fact that various regulations mention acupuncture suggestions, the quality of those recommendations varies, and there are no internationally acknowledged regulations governing acupuncture treatment regimens.…”
Section: Introductionmentioning
confidence: 99%